The Concept of Muḥammad Shaḥrūr on Gender Parity in Inheritance Legislation - Huda, Miftahul; Hidayati, Tri Wahyu (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The distribution of inheritance by Islamic law is carried out equitably, namely by allocating shares to both males and females. Nevertheless, the current discussion surrounding the allocation of inheritance is facing challenges, particularly about the inequitable division of inheritance, where two males receive twice as much as one female. This disparity is perceived as unjust by certain individuals. Various experts have extensively analyzed both male and female issues. This analysis provides a thorough examination of Muḥammad Shaḥrūr's ideology, focusing on its normative legal aspects, particularly about gender and legal concepts. As per Muḥammad Shaḥrūr, Allah assigns at least fifty percent of a man's share to a woman. This minimum level applies in cases where the mother does not provide any financial support for the family's maintenance. Nevertheless, if women actively participate in creating revenue and contribute to the family's financial support, their share of contribution becomes comparable to that of males. Muḥammad Shaḥrūr contends that both men and women can obtain equal portions of inheritance within the framework of gender and legal principles. However, this equality is dependent on certain conditions and must not violate the specified limits set by Islamic law.